Penyelenggaraan Pelatihan Fardu Kifayah oleh KKN Kelompok 64 UINSU guna Meningkatkan Pengetahuan Masyarakat Desa Tiganderket Kec. Tiganderlet Kab. Karo - Zahra Saritza; Susilawati Siregar (VISA: Journal of Vision and Ideas, 2023)
This article is the result of the dedication of UIN-SU students from the KKN 64 group to the community regarding the implementation of fardu kifayah in Tiganderket Village, Tiganderket District, Karo Regency with the problem of lack of understanding and community courage in implementing fardu kifayah so that it is very possible to hold training. The importance of this training is to educate the public regarding the procedures for caring for corpses, because in this modern era these kinds of religious activities have begun to be abandoned.The purpose of this training is to be able to share experiences and lessons with the Tiganderket community about fardu kifayah including: bathing, mourning, praying, and burying. The method used is a field or qualitative method with a descriptive approach.